Alternatives to slash-and-burn - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Estimates indicate that more than 200 million landless people have migrated into tropical forests in recent decades, and that these numbers are increasing. Farmers who cultivate the land can no longer give it time to fully recover; fallow periods...